Giacomo Puccini in Odessa Opera: history and modernity - Ostroukhova, Nataliia (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
Relevance of the study. The role and place of the operas by Giacomo Puccini in the repertoire of the Odessa Opera are examined. The concept of verism as the new opera direction in the end of XIX century is revealed. The performances of ten operas by G. Puccini that were performed on Odessa stage during 1898-2024 are studied. The retrospective of the change of the art generations on Odessa scene is analyzed. Main objective(s) of the study. The topic of this publication is demonstration of the role and meaning of operas by G. Puccini in the context of the development of the genre and style specifics of the repertoire of the Odessa Opera. The scientific novelty of the research is that for the first time the panoramic observation of the performance of the operas by G. Puccini that determined the practical experience and artistic traditions of the Odessa Opera house in the performance of the pieces of verist and neoclasslical directions was created. Methodology. This research is based on the systematic approach as the expression of the dialectic method that allows to unite the source-scientific, historiographical and analytical aspects of the musicological study. Results. Giacomo Puccini is called the last outstanding Italian composer of the edge of 19– 20 centuries who completely dedicated himself to the opera genre. Opera style of Puccini evolved from verist dramas to chamber opera of the beginning of the 20 century. The fair recognition of the Italian opera school as the historical and stylistic basis of the European opera art explains the deep reasons for the dominant role of the Italian opera in the Odessa opera practice of the times of the entrepreneurship. But historically in happened so that in 1926 the Ukrainian opera steadily joined the repertoire of Odessa State Academic Theater of Opera and Ballet and becomes its systematic genre and stylistic basis. One of the most fruitful for the creative practice of the Odessa National Academic Theater of Opera and Ballet is the development of two main genre and stylistic directions of Odessa opera practice — the Italian romantic opera (including its extreme verist-expressionist expression) and the Ukrainian romantic and neo-romantic opera, which later received recognition as a national opera classic.